THE RELATIONS OF PSYCHOLOGICAL-EMOTIONAL SPHERE WITH PHYSIOLOGICAL INDICATORS FOR WOMEN HAVING REPRODUCTIVE DISORDERS - Sirakovska, Olena (PSYCHOLOGICAL JOURNAL, 2020)
The article highlights the problem of the relations between the psychological-emotional sphere and physiological indicators for women having reproductive disorders. The reproductive problems are multifaceted and multidimensional, and their psychological component is more and more important in the recent decades, due to demographic problems and increased cases of women’s infertility.The conducted theoretical analysis of scientific works allowed us to determine the following main psychological-emotional characteristics of the studied women: emotional sensitivity, emotional lability, severe negative emotions, increased personal and reactive anxiety, pessimism and mood variability, high emotional instability and impulsivity, behavioural rigidity, variable emotions at the premenstrual period.The empirical study involved 204 women of childbearing age with reproductive disorders, their average age was 29.4 years, and their diagnoses were: inflammatory processes, hormonal imbalance, neoplasms, infertility. The studied women had violated psychological-emotional states, severe negative emotions, which cause further deterioration of their reproductive health. The feelings of guilt and shame at women with reproductive disorders were accompanied by a suppressed mood background, deterioration of well-being and decreased activity.The women with reproductive disorders had clearly changed physiological parameters, namely, increased blood pressure, heart rate and decreased reserve of the cardiovascular system. They indicated the women’s worsened physical health and their deteriorated psychological-emotional sphere. We determined that the worsened physiological state of women with gynaecological problems can lead to violated homeostasis, deteriorated physical and mental health and it requires mandatory medical and psychological intervention.